El porvenir de las razas: El racialismo en el Perú entre los siglos XIX y XX (2019)
This article aims to show the relationship between scientific discourses andthe strategies of power that established an exclusionary hierarchy in Peruviansociety at the beginning of the 20th century. Therefore, the practices developedby the oligarchy and other forms of power in the aforementioned context areexamined. Likewise, the article is divided into four parts. First, we will reviewthe main theses of French racialism, particularly the investigations of GustaveLe Bon and Alfred Fouillée. Second, the French influence on the racialist proposalsof Javier Prado and Clemente Palma will be shown. Third, considering theproposed objective, the cultural and political strategies that built an indigenousidentity for specific purposes will be examined. Finally, certain questions willbe raised that allow us to discuss the possibilities of expanding the history ofideas towards a genealogy of practices.